Learning Automata-Based Algorithm as a Solution to the Problem of Priority-Based Target Coverage in Directional Sensor Networks with Adjustable Sensing Ranges - Norsyarizad Razali, Mohd; Salleh, Shaharuddin; Azzeri Md Naiem, Mohd (International Journal of Engineering and Technology, 2018)
The limited battery power and sensing angle of directional sensors makes maximizing the network lifetime of directional sensor networks (DSNs) a challenging problem, especially when surveillance of a set of targets in a given area is involved. Sensors with multiple ranges and targets that require varied coverage further exacerbate this problem. This study refers to this problem as PTCASRâ€”Priority-based Target Coverage with Adjustable Sensing Ranges. A promising solution to this problem is to use a scheduling technique, which involves allocation of sensors into cover sets and their successive activation thereafter. A scheduling algorithm based on learning automata is proposed in this study as a solution to this problem. To assess the performance of the proposed algorithm in extending network lifetime, several simulations were conducted.Â  Â